Association between the functional movement screen and knee valgus moments during a sidestep-cut : implications for ACL injury prevention - Sim, Sophia Feng-en (2016)
Sidestep-cut is a main mechanism of non-contact Anterior Cruciate Ligament (ACL) injuries that can result in high knee valgus moments (KVM), which can independently cause the ACL to rupture. The Functional Movement Screen (FMS), a battery of seven tests, has proven to predict injury risk. However, the association between FMS test scores and KVM has yet to be investigated. This study aims to find an association between FMS test scores and peak KVM during an unplanned bilateral sidestep-cut and its implication on non-contact ACL injury prevention. It was hypothesised that FMS test scores would have a strong correlation with peak KVM. The lower the FMS scores, the greater the KVM exhibited when executing the sidestep-cut. 15 injury-free Singapore Opens team netballers (Age: 24.6±2.5; Height: 1.75±0.06m; Body mass: 63.2±7.4kg) participated in a series of sidestep-cuts and a modified FMS test in a randomised order. Peak KVM during weight acceptance phase was obtained using a 12-camera three-dimensional motion capture system. A modified, six-component FMS test, with the removal of the shoulder mobility component, was scored based on a half- point scoring system. There was no significant correlation between peak KVM and the modified FMS composite and component scores. Practitioners should not use the FMS to assess non-contact ACL injury risk via sidestepping with the current scoring criteria. Future studies should increase scoring specificity by expanding the FMS scoring criteria to include a wider spectrum of scores, and examine the relationship between peak KVM and scores of other easy-to-administer tests.